Sociocultural Landscape of the Pomor Coast of the White Sea through the Lens of Collective Nicknames - Valeria Stanislavovna Kuchko (Вопросы ономастики, 2024)
This article is based on field data collected in September 2023 by the Toponymic Expedition of Ural Federal University (Ekaterinburg). The research was conducted in several settlements along the Pomor coast of the White Sea in the Belomorsky District of Karelia, including Sumskiy Posad, Kolezhma, Lapino, and Belomorsk. The paper presents some of the expedition’s findings on how collective nicknames and related narratives reflect the region’s history, culture, and social, ethnic, and religious characteristics. The article examines the microsystem of local group nicknames used along a segment of the Pomor coast. These nicknames include repoedy from Shueretskoye, kochegary from Virma, meshchane and tserkovnye srali from Sumskiy Posad, lopari from Kolezhma, and tsari and vory from Nyukhcha. It also considers nicknames from inland villages near the Pomor and mainland border, such as repniki from Lapino, vshiviki from Korosozero, pisanye batogi from Pulozero, and lindushniki from Endoguba. The article notes the factors contributing to the prevalence of local names on the White Sea coast, particularly on the Pomor coast, compared to mainland regions of the Russian North and other traditionally agricultural areas. The study explores the motivations behind the nicknames that persist in the collective memory of the Pomor coast’s older residents (the expedition’s informants). It suggests explanations for several collective nicknames, describing the historical and sociocultural context in which and thanks to which they emerged, based on historical and ethnographic sources.